ITIL® 4 Direct, Plan and Improve (DPI) Your Companion to the ITIL 4 Managing Professional and Strategic Leader DPI Certification - Agutter, Claire (IT Governance Ltd, 2021)
ITIL® 4 Direct, Plan and Improve (DPI) is a study guide designed to help students pass the ITIL® 4 Direct, Plan and Improve module. It provides students with the information they need to pass the exam, and help them become a successful practitioner, with additional guidance throughout which they can lean on once their training and exam are over.